2015
DOI: 10.1093/cid/civ694
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of UncomplicatedChlamydia trachomatisInfections in Adolescents and Adults: Summary of Evidence Reviewed for the 2015 Centers for Disease Control and Prevention Sexually Transmitted Diseases Treatment Guidelines

Abstract: In preparation for the 2015 Centers for Disease Control and Prevention (CDC) Sexually Transmitted Diseases (STD) Treatment Guidelines, the CDC convened an advisory group in 2013 to examine recent abstracts and published literature addressing the epidemiology, diagnosis, and management of STDs. This article summarizes the key questions, evidence, and recommendations for the diagnosis and management of uncomplicated Chlamydia trachomatis (CT) infection in adolescents and adults that were considered in developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…However, very recently Horner et al [ 23 ] have shown that the waning of CT Pgp3 antibodies is less than 5% over 12 years, which suggests only a very modest effect of waning of CT antibodies. Use of NAAT based diagnosis of CT, might have alleviated some of these limitations caused by the suboptimal sensitivity and specificity of serological tests, but such results were not available [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, very recently Horner et al [ 23 ] have shown that the waning of CT Pgp3 antibodies is less than 5% over 12 years, which suggests only a very modest effect of waning of CT antibodies. Use of NAAT based diagnosis of CT, might have alleviated some of these limitations caused by the suboptimal sensitivity and specificity of serological tests, but such results were not available [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A test of cure is not recommended after completing treatment unless symptoms persist or if reinfection is suspected. However, testing sooner than 3-4 weeks post therapy completion may not be valid because of persisting, residual pathogen-derived nucleic acids 130131. Treatment usually resolves infection but does not ameliorate preexisting inflammatory-mediated tissue damage.…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Persisting C. trachomatis infections could be detected by performing a test of cure (TOC) after treatment. Current chlamydia treatment guidelines recommend a TOC between 3 and 4 weeks after initiation of treatment, in certain patient groups or when symptoms persist [ 4 , 7 , 10 ]. However, up to 90 % of chlamydia infections are asymptomatic, which could lead to persisting infections remaining undetected [ 4 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%